2006
DOI: 10.1128/aem.00160-06
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Ether Pollutants by Pseudonocardia sp. Strain ENV478

Abstract: A bacterium designated Pseudonocardia sp. strain ENV478 was isolated by enrichment culturing on tetrahydrofuran (THF) and was screened to determine its ability to degrade a range of ether pollutants. After growth on THF, strain ENV478 degraded THF (63 mg/h/g total suspended solids [TSS]), 1,4-dioxane (21 mg/h/g TSS), 1,3-dioxolane (19 mg/h/g TSS), bis-2-chloroethylether (BCEE) (12 mg/h/g TSS), and methyl tert-butyl ether (MTBE) (9.1 mg/h/g TSS). Although the highest rates of 1,4-dioxane degradation occurred af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
139
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(147 citation statements)
references
References 40 publications
7
139
0
1
Order By: Relevance
“…8) (28). The lack of sustained 14D oxidation in THFgrown Pseudonocardia ENV478 has been suggested to be due in part to the generation of intermediates such as 2-hydroxyethoxyacetic acid (45). This acid is thought to be generated from 2-hydroxyethoxy-2-acetaldehyde, which is the tautomer of the immediate hydroxylated product of 14D oxidation, 1,4-dioxane-2-ol (45).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…8) (28). The lack of sustained 14D oxidation in THFgrown Pseudonocardia ENV478 has been suggested to be due in part to the generation of intermediates such as 2-hydroxyethoxyacetic acid (45). This acid is thought to be generated from 2-hydroxyethoxy-2-acetaldehyde, which is the tautomer of the immediate hydroxylated product of 14D oxidation, 1,4-dioxane-2-ol (45).…”
Section: Discussionmentioning
confidence: 99%
“…Because this chlorinated hydrocarbon is one of the most frequently encountered groundwater pollutants in the United States, there is concern over the environmental fate of cyclic ethers that are likely cocontaminants at sites contaminated with 1,1,1-trichloroethane (27,40,44). Currently, 14D is not known to be used widely as a growth substrate by microorganisms, but a number of studies have demonstrated that 14D can be oxidized cometabolically by aerobic organisms that grow on THF or other substrates, such as toluene or n-alkanes (4,28,45,49). Notably, this group of organisms includes Mycobacterium vaccae JOB5 (4) and Pseudonocardia sp.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…ENV478 tetrahidrofuránon nőtt tenyészete az MTBE-t TBA-vá oxidálta [103]. A reakciót valószínűleg a törzs tetrahidrofurán monooxigenáz enzime katalizálta, mely az alkán hidroxilázok rokonsági körébe tartozik.…”
Section: Az éTer Típusú üZemanyag-adalékok Kometabolikus Bontásaunclassified